Recent advances in the treatment of non-small cell lung cancer with MET inhibitors - Dongna Zhang; Wenying Zhang; He Liu; Pan Liu; Chunxin Li; Yangyang Liu; Jicheng Han; Guangze Zhu (Frontiers in Chemistry)
Recently, research into the oncogenic driver genes associated with non-small cell lung cancer (NSCLC) has advanced significantly, leading to the development and clinical application of an increasing number of approved therapeutic agents. Among these, small molecule inhibitors that target mesenchymal-epithelial transition (MET) have demonstrated successful application in clinical settings. Currently, three categories of small molecule MET inhibitors, characterized by distinct binding patterns to the MET kinase region, have been developed: types Ia/Ib, II, and III. This review thoroughly examines MET’s structure and its crucial role in NSCLC initiation and progression, explores discovery strategies for MET inhibitors, and discusses advancements in understanding resistance mechanisms. These insights are anticipated to enhance the development of a new generation of MET inhibitors characterized by high efficiency, selectivity, and low toxicity, thereby offering additional therapeutic alternatives for patients diagnosed with NSCLC.